Maternal Blood Trace Element Levels in Preeclampsia: Comprehensive Systematic Review and Meta-Analysis - Wening Hapsari; Achmad Januar Er Putra (Asian Journal of Health Research, 2022)
Introduction: Deficit in trace elements was frequent in pregnant women and could lead to preeclampsia development. This meta-analysis aimed to determine calcium, magnesium, zinc, iron, and copper serum levels in preeclampsia women compared to healthy pregnant women. Methods: A systematic search is conducted in PubMed, ScienceDirect, and Google Scholar from inception into March 25th, 2022 using keywords of “("calcium" OR "magnesium" OR "zinc" OR "copper" OR "iron" OR "trace element" OR "trace elements") AND ("serum" OR "blood") AND ("preeclampsia")”. Articles obtained from PubMed, ScienceDirect, and Google Scholar were 62, 31, and 119 respectively.  The article screening process was based on the PRISMA 2020 guidelines. Study quality was assessed using NOS. Results: Fifty-four studies were included in this systematic review. Pooled analysis revealed that serum calcium (SMD = (-1.66; 95% CI = -2.05 to -1.28, magnesium (SMD = -1.28; 95% CI = -1.37 to -1.20, and zinc were significantly lower in preeclampsia (SMD = -2.4; 95% CI = -4.11 to -0.7. Serum iron was higher in preeclampsia (SMD = 1.71; 95% CI = 0.21 to 3.21). No significant different difference in serum copper level. Conclusion: The mean blood levels of calcium, magnesium, and zinc were considerably lower, while blood iron levels were higher in preeclamptic women compared to the healthy pregnant group. Copper levels were not significantly different between the two groups.